Atipical association case between dens in dente and twinning - Menezes, Vinícius Cesar Barbosa de; Abreu, Saulo; Resende, Thalles Diniz D`Avila; Amaral, Fabrício Resende; Azevedo, Carolina Drumond de Barros e; Greco, Alexandre Camisassa Diniz Leite (Journal of Oral Diagnosis, 2019)
The formation of the tooth, called Odontogenesis, results from the interaction of the oral epithelium and the ectomesenchyma, where this complex process follows a histological pattern at each stage of this development, thus forming structures such as enamel, dentin, pulp, cementum, periodontal ligament and alveolar bone. And in determinatated circumstances, modifications in the process of tooth development alter the morphology of the tissues, forming dental anomalies such as twinning, fusion, concrescence and Dens in Dent (Invented Tooth). Therefore, the objective of this study is to report a rare case of the presence of associated dental anamolies, twinning and Dens in Dent, diagnosed by Cone Beam Computed Tomography (CBCT).